Unearthing anti-MRSA agents from alpine lichens: discovery and characterization of bioactive compounds in Cetraria islandica from the snowy Cangshan region - Lu, Junlin; Tian, Hongqiao; Liang, Fangrong; Xiang, Zhiyi; Liu, Menglong; Ding, Haiyan (Frontiers in Microbiology, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA)—declared a WHO priority pathogen—remains a global menace, yet no new-scaffold agent has reached the clinic in two decades. The under-investigated chemical reservoir of lichens was tapped by targeting Cetraria islandica collected in Cangshan, Yunnan. Bioassay-guided fractionation yielded lichesterinic acid (C19H32O4, 95% purity, 0.32% yield), whose structure was elucidated by 1H/13C NMR and HRESI-MS. Antimicrobial spectrum testing revealed that lichesterinic acid exhibited a minimum inhibitory concentration (MIC) of 64–128 μg/mL against Staphylococcus aureus, MRSA, and Listeria seeligeri and an inhibitory rate greater than 70% against phytopathogenic fungi such as Sclerotinia sclerotiorum and Valsa mali. When combined with six different antibiotics, it exhibited synergistic or additive effects, suggesting its potential to restore sensitivity to traditional antibiotics. Cytotoxicity assays of HepG2 and Vero cells showed IC50 values of 1,854 and 1,771 μM, respectively. Acute oral toxicity tests in mice revealed no deaths or significant toxicity, with an LD50 > 5,000 mg/kg, indicating that the drug was nontoxic. Molecular docking studies revealed that lichesterinic acid may stabilize key resistance proteins such as deacetylase (def) and PBP2a, potentially exerting multitarget antimicrobial effects by inhibiting protein synthesis and cell wall formation. In summary, lichesterinic acid is a safe, low-toxicity, broad-spectrum candidate for a new type of natural antimicrobial agent, providing a material basis and theoretical foundation for the development of MRSA drugs.